EXPLORING THE ROLES AND LEADERSHIP BEHAVIOR OF CHIEF INFORMATION OFFICERS (CIOS): CASE STUDIES OF TWO PUBLIC UNIVERSITIES IN MALAYSIA - Waheed, Hussain (Journal of Information Systems and Digital Technologies, 2022)
Chief Information Officer (CIO) plays a very important role in an organization as CIO is the IT leader who ensures effective IT employment in organizations. The aim of this study was to explore the roles and leadership behaviors of the CIO in HEIs in Malaysia. This study, which employed semi-structured one-on-one interviews, was conducted with former and current CIOs of two public universities of Malaysia. The interviews were transcribed, and the interview data were analyzed thematically. The results indicated that the main role of CIOs is managing IT infrastructure, handling HEI’s IT requirements, governance of IT in HEIs and strategic planning. It is also found that CIOs should have interpersonal skills, IT knowledge, managerial knowledge and skills and knowledge about HEIs’ requirements. Furthermore, CIOs should exhibit Transformational and Transactional leadership behaviors to be effective IT leaders.